Pengaruh Kepemimpinan, Pelatihan dan Komitmen Kerja terhadap Kinerja Karyawan pada Koperasi Simpan Pinjam Credit Union Semarong Kabupaten Sanggau Provinsi Kalimantan Barat - Arezzo, Ardias (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The study aims to evaluate the impact of leadership, training, and job commitment on employee performance at KSP Credit Union Semarong, Sanggau District, West Kalimantan Province. The research employed a quantitative, descriptive approach. Data were collected through a questionnaire using an ordinal Likert scale (range 1 to 5) distributed among 296 employees of KSP Credit Union Semarong, with a sample of 170 respondents selected using the Slovin approach. Data analysis utilized multiple linear regression. The findings indicate that leadership, training, and job commitment significantly influence employee performance at KSP Credit Union Semarong. Enhancements in these three factors can lead to improved employee performance, thereby benefiting KSP Credit Union Semarong in achieving its organizational goals.